Comparative analysis of transcriptional regulation of the FOXP2 gene between humans and chimpanzees - Caporale, Alfredo Leandro (2016)
Understanding the evolution of the human brain is one of the greatest challenges that science faces today. The genetic changes that led to the acquisition of new functional capabilities of our brain are encoded in our genome. Our hypothesis is that the acquisition of new expression patterns in the human lineage of genes involved in the development and functioning of the brain would have been critical for the evolution of our unique cognitive capacities. Using public databases of human accelerated conserved non coding sequences (HAEs or human accelerated elements), we found that the locus of forkhead box P2 (FOXP2) transcription factor contains 6 HAEs, being into the top10 genes with highest number of HAEs, along with some of their putative regulatory targets (RBFOX1, CNTNAP2). Furthermore, this gene has been shown to be critical for normal development of language in humans. Mutations in FOXP2 cause developmental verbal dyspraxia (DVD), and two functional copies of the gene be necessary for a correct development of fluent speech. In this work, we comparatively analyze the 6 HAEs present at this locus through bioinformatics tools, to determine in silico potential transcription factors that would be binding and regulating differentially this gene in humans and chimpanzees. In addition, we functionally characterize these elements through the generation of transgenic zebrafish lines carrying the human or chimpanzee sequence. Through this first approach, we expect to find any difference (gain or loss of function) in the pattern of expression of the reporter protein between orthologs, and to link it to new areas of expression of the FOXP2 gene, and thus may have contributed to the emergence and development of human neuroanatomical features associated with language.